2022
DOI: 10.1186/s12866-022-02460-x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Infections: a novel porcine wound model to evaluate treatment efficacy

Abstract: Candida albicans is a common cause of opportunistic mycoses worldwide and a major contributor in wound infections. The purpose of this study was to establish a fungal wound model and analyze the effects of a common antifungal agent against the proliferation of three C. albicans strains. Second degree burns were created, and then inoculated with one of three different C. albicans ATCC strains: 10261 reference strain, 64550 fluconazole resistant and 26310 fluconazole sensitive. After fungal inoculation, every wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Developing an effective wound dressing against C. albicans is crucial for the treatment of life-threatening infections in burn patients . Our results indicated that nanofibers containing 50 and 100% propolis can be effective when used as potential wound dressings in S.…”
Section: Resultsmentioning
confidence: 73%
“…Developing an effective wound dressing against C. albicans is crucial for the treatment of life-threatening infections in burn patients . Our results indicated that nanofibers containing 50 and 100% propolis can be effective when used as potential wound dressings in S.…”
Section: Resultsmentioning
confidence: 73%
“…Recent studies have shown that C. albicans is a 22% infectious agent in chronic wounds. [ 79 ] Within the scope of the study, the antimicrobial activity of the membrane, which gave the best results, on pathogens found at risk in wound sites was investigated. While no antimicrobial activity was observed on gram negative pathogens ( E. coli , E. aerogenes and K. pneumonia ), high activity was determined on S. aureus (21.5 mm) and C. albicans (16.0 mm) (Table 6 and Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila melanogaster , Caenorhabditis elegans , and Galleria mellonella) have been applied to candidal biofilm studies, each of them having advantages and disadvantages (172). There are a significant number of studies using mammalian animal models, such as the rat indwelling catheter model (8) and a rabbit catheter model (173), in addition to porcine wound models (174). While these are all immensely useful, they are costly and can prohibit progress in evaluating new innovative therapies.…”
Section: Innovative and Accessible Animal Models For The Study Of Can...mentioning
confidence: 99%